Effect of OSAS on cerebral vasoreactivity and cIMT before and after CPAP treatment. (24th July 2019) - Piraino, Alessio; Sette, Giuliano; D'Ascanio, Michela; La Starza, Sara; Aquilini, Mauro; Ricci, Alberto
Abstract: Introduction: Obstructive sleep apnea syndrome (OSAS) has been shown to be an important risk factor for ischaemic cerebral disease. Specific Doppler parameters may be used to measure cerebral vascular dynamics opening the door to new markers/predictors of risk. The objective of our study was to shed light on how the treatment of OSA with continuous positive airway pressure (CPAP) may have an impact on these parameters and, consequently, lower the risk of cerebral ischemic events in these patients. Methods: A total of 40 untreated patients diagnosed with moderate to severe obstructive sleep apnoea were submitted to a comprehensive ultrasonographic transcranial Doppler evaluation. The parameters measured were: Breath holding index (BHI), mean blood flow velocity (MBFV) and pulsatility index in middle cerebral artery. Colour Doppler ultrasound was also used to measure carotid intima‐media thickness (cIMT). These parameters were compared before and after CPAP treatment. Results: After CPAP treatment, MBFV and BHI were shown to be increased (without statistical significance), while cIMT and polysomnographic parameters were significantly decreased. Conclusion: The improvement of cerebral vasoreactivity parameters and cIMT after long‐term CPAP treatment suggest that treatment of OSA may influence the cerebral vascular regulation and consequently reduce the risk of stroke.